2018
DOI: 10.5935/0004-2749.20180006
|View full text |Cite
|
Sign up to set email alerts
|

Weight reduction for a better visual outcome in idiopathic intracranial hypertension

Abstract: Weight reduction combined with medical treatment is associated with significantly better improvement in visual acuity, visual field, and papilledema in idiopathic intracranial hypertension patients. Compliance with an efficient diet program should be encouraged in overweight patients with idiopathic intracranial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…The greatest weight loss with a lifestyle intervention was reported using a very low-energy diet (VLED) dietary intervention with a 15.7 kg at 3 months (Level 2+ 6 ). Short-term dietary interventions resulted in modest reductions in BMI of 2.0–2.3 kg/m 2 at 3–6 months (Level 2− to 2+ 26,29 ). At a median of 10–11 months of follow-up of a dietary intervention, weight loss was not significant; however, the addition of 2.25 g/d of metformin led to a mean weight loss of 6.9% and 8.2% in patients with hyperinsulinaemia and polycystic ovary syndrome, respectively (Level 2+ 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greatest weight loss with a lifestyle intervention was reported using a very low-energy diet (VLED) dietary intervention with a 15.7 kg at 3 months (Level 2+ 6 ). Short-term dietary interventions resulted in modest reductions in BMI of 2.0–2.3 kg/m 2 at 3–6 months (Level 2− to 2+ 26,29 ). At a median of 10–11 months of follow-up of a dietary intervention, weight loss was not significant; however, the addition of 2.25 g/d of metformin led to a mean weight loss of 6.9% and 8.2% in patients with hyperinsulinaemia and polycystic ovary syndrome, respectively (Level 2+ 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 6 studies 7,20,21,31-33 of randomized control trials (RCTs), 4 prospective nonrandomized interventional studies, 6,24,25,30 and 2 prospective 27,29 and 4 retrospective observational studies. 5,22,23,26,28 Prescribed concomitant IIH pharmacotherapy is presented in eTable 1 (links.lww.com/WNL/D149).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Celebisoy N. and co-authors [16] showed visual field improvement on either acetazolamide or topiramate considering that the two medications exert their effect through the carbonic anhydrase inhibition. Nevertheless, Koc F and his colleagues 2018 [17] showed in their recent study that the weight reduction combined with acetazolamide significantly improve the visual field in IIH patients. The discrepancy in the results could be attributed to different methodology applied in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…A paciente do relato, de 53 anos, estava na menopausa e fazia uso de reposição hormonal. Dessa forma, torna-se necessário e deve ser encorajado nesses pacientes um programa de perda de peso através de dieta, exercício e intervenção comportamental, associado a tratamento medicamentoso que reduza a produção de LCR 10,11 .…”
Section: Discussionunclassified